2021
DOI: 10.1002/cae.22408
|View full text |Cite
|
Sign up to set email alerts
|

Socrative, a powerful digital tool for enriching the teaching–learning process and promoting interactive learning in Chemistry and Chemical Engineering studies

Abstract: Mobile learning is an emerging educational methodology that requires an updated conceptualization to yield effective pedagogical approaches that may enrich the teaching-learning processes. The present research aimed to better understand and to assess the effectiveness of mobile learning in Science and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
2
13
0
3
Order By: Relevance
“…The results showed that children (aged from 6 to 9 years old) were motivated to learn mathematics and geometry concepts, and demonstrated mathematical thinking and geometric thinking with integrated learning materials and activities that required a hierarchical procedure of concreteabstract-concrete thinking (Liu & Cummings, 2001). Some other such integrative studies were also found in the literature, such as the integration of science and mathematics at secondary school level (Prieto et al, 2019), chemistry and chemical engineering studies at university level (Roman et al, 2021), among the four areas of STEM (Becker & Park, 2011;Shirey, 2018). The studies over years showed positive outcomes.…”
Section: Integrative Approaches Among S-m-ementioning
confidence: 87%
See 1 more Smart Citation
“…The results showed that children (aged from 6 to 9 years old) were motivated to learn mathematics and geometry concepts, and demonstrated mathematical thinking and geometric thinking with integrated learning materials and activities that required a hierarchical procedure of concreteabstract-concrete thinking (Liu & Cummings, 2001). Some other such integrative studies were also found in the literature, such as the integration of science and mathematics at secondary school level (Prieto et al, 2019), chemistry and chemical engineering studies at university level (Roman et al, 2021), among the four areas of STEM (Becker & Park, 2011;Shirey, 2018). The studies over years showed positive outcomes.…”
Section: Integrative Approaches Among S-m-ementioning
confidence: 87%
“…In the literature of SME learning, some studies were conducted to examine STEM learning as a combined focus (Seage & Türegün, 2020), and some pursued an integrative approach to analyze studies on technology-based learning in science, mathematics and engineering together (Becker & Park, 2011;Roman et al, 2021). This study employed such integrative approach.…”
Section: Integrative Approaches Among S-m-ementioning
confidence: 99%
“…Uno de los aspectos más beneficiosos de Socrative es que permite hacer preguntas y obtener las respuestas del alumnado con inmediata retroalimentación e información estadística (Dervan, 2014), pudiendo dar feedback directo o hacer comentarios junto con la respuesta correcta, y posibilitando mostrar en el aula los resultados generales de todo el grupo, bien pregunta por pregunta o al finalizar el cuestionario (Serrano y Casanova, 2018). Son muchas las investigaciones realizadas en torno a esta aplicación (Abdulla, 2018;Balta et al, 2018;Balta y Tzafilkou, 2019;McKenzie y Ziemann, 2020;Roman et al, 2021, son algunas de las más recientes) y su principal ventaja, según Balta y Tzafilkou (2019), además de la integración de la tecnología en el aula, es el aumento del compromiso, la motivación y el aprendizaje de los estudiantes. Sin embargo, Dervan (2014) menciona que se deben tener en cuenta posibles aspectos negativos como problemas técnicos con el software (falta de conexión o interrupción durante la prueba), falta de experiencia del profesorado o ansiedad del alumnado al incluir las puntuaciones de estas pruebas en su calificación general, entre otras.…”
Section: Socrative Como Herramientaunclassified
“…A gamificação tem ganhado espaço na educação e estudos tem demonstrado a efetividade dessa prática, como o realizado por López-Jiménez et al (2021), que concluiu, em seu estudo, que houve diferença significativa na nota dos exames finais de anatomia humana de estudantes que usaram ferramentas de gamificação em relação aos que estudaram de maneira convencional, sendo observado, inclusive, maior motivação na participação nas aulas (López-Jiménez et al, 2021). Nesse sentido, o estudo de Roman et al (2021) demonstrou resultado parecido com o uso da plataforma Socrative, que ajudou a estabelecer os conceitos de química e diminuiu a queda na curva de atenção do público, obtendo assim o máximo de quase toda a sessão.…”
unclassified
“…A plataforma Socrative é um ambiente virtual de ensino-aprendizagem acessível, que possibilita ao docente a elaboração de atividades complementares ao ensino tradicional e aos discentes uma tarefa interativa com feedback em tempo real (Oliveira & Torrentes, 2021). Além de se mostrar uma ferramenta muito útil no processo de ensino-aprendizagem, o Socrative apresenta alta aceitabilidade pelos estudantes, que acreditam que os questionários da plataforma aumentam a motivação e atenção em aula, assim como o entendimento dos conceitos apresentados na teoria (Roman et al, 2021).…”
unclassified